Anti-inflammatory, analgesic and antioxidant activities of novel kyotorphin-nitroxide hybrid molecules. Issue 8 (15th April 2016) - Bi, Wei; Bi, Yue; Gao, Xiang; Yan, Xin; Zhang, Yanrong; Xue, Ping; Bammert, Catherine E.; Legalley, Thomas D.; Michael Gibson, K.; Bi, Lanrong; Wang, Jia-Xiang
Graphical abstract: Abstract: Mitochondrial oxidative damage contributes to a wide range of pathologies, including ischemia/reperfusion (I/R) injury, cardiovascular disorders and neurodegenerative diseases. Accordingly, protecting mitochondria from oxidative damage should possess therapeutic relevance. In the present study, we have designed and synthesized a series of novel kyotorphin-nitroxide hybrid molecules, and examined their free radical scavenging activities, in addition to their anti-inflammatory and analgesic activities. We have further characterized these compounds in a simulated I/R cellular model. Our findings suggest that the protective effects of kyotorphin-nitroxides partially reside in maintaining optimal mitochondrial function.